(untitled) (Papeles, 2025)
Introduction: This article analyzes the teaching and learning process within the Mathematics course at the Universidad Pedagógica Nacional Francisco Morazán, aiming to identify the methodological strategies applied by teachers, the challenges faced in the educational process, the teaching of the statistics block, and the knowledge of the Project-Based Learning (PBL) approach. Methodology: The research followed a qualitative approach, exploratory in nature, and phenomenological in design. Semi-structured interviews were conducted with 17 teachers from different UPNFM campuses who have taught the Mathematics course in humanities-related degree programs. Results and Discussion: Findings show that the most commonly used strategies include technology integration, problem-solving, and teamwork. However, student motivation and attitudes, along with weak prior knowledge, represent the main difficulties. In the statistics block, insufficient time was identified as a major issue, with practical contextualization and the use of software like GeoGebra being the most applied strategies. Although many teachers are aware of project based learning, only a few have implemented it, highlighting benefits such as meaningful learning. Conclusions: It is necessary to strengthen the educational process in these pedagogical spaces through innovative strategies that promote participation, motivation, and deep understanding of mathematics, taking into account the particularities of the university context.